Advances in dynamic metrology using in-line digital holographic Interferometry - Singh, Vijay Raj (2011)
In this paper a lensless in-line digital holographic microscope is presented as interferometric applications for dynamic measurements. A diverging beam is used to illuminate the object to get the required magnification. In particular, time average in-line digital holographic interferometry is studied for vibration measurements of a smaller membrane. The sensitivities of the numerically reconstructed amplitude and phase information are studied with the distance from object to the CCD, during hologram recording. It is shown that, the increase in object recording distance results the increase in the sensitivity of the Bessel type of fringes representing the vibration amplitude information, while it shows the opposite behaviour for phase information which represent the mean deformation fringes. To explain this phenomenon, the samplings of the interference of object and reference beams, and of the diffracted speckled wavefront from the object are individually studied. A double exposure approach is used for the suppression of noise from real image wave caused by zero-order term and twin image waves because of in-line geometry. The experiment is performed for the study of vibration behaviour of harmonically excited aluminium membranes of 5 mm in size and results are presented.